Tanggung Jawab Komisi Pemilihan Umum Atas Kegagalan Pelindungan Data Pribadi Dalam Pemilihan Umum Tahun 2024 - Tri Wibowo, Muhammad Kunto (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The 2024 General Election is held by utilizing the development of ICT. This presents a potential threat related to the Protection of Voters' Personal Data. In the implementation of the 2024 General Election, there was a failure to protect the Personal Data of Voters originating from SIDALIH. Therefore, this study aims to identify the responsibilities of the KPU as the Controller of Personal Data in the implementation of the 2024 General Election. The research was conducted using a normative juridical approach method with descriptive analytical research specifications. The author implements normative law against facts and practices that occur in the field. The data collection technique used in this research is a literature study that serves to collect information about Personal Data Protection and the organization of elections.The result of this study shows that the responsibility of the KPU towards the failure of Voters' Personal Data Protection in the implementation of the Election is present when the KPU cannot prove that it has implemented the obligation of Voters' Personal Data Protection properly. Then, the legal responsibility given to the KPU for the failure of Voters' Personal Data Protection is in the form of administrative sanctions which are enforced through the Personal Data Protection Agency.